2022
DOI: 10.3389/fimmu.2022.1005937
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and indoleamine-2,3-dioxygenase as potential adjuvant targets for Papillomavirus-related tumors immunotherapy

Abstract: High-risk Human papillomavirus (HPV) infections represent an important public health issue. Nearly all cervical malignancies are associated with HPV, and a range of other female and male cancers, such as anogenital and oropharyngeal. Aiming to treat HPV-related tumors, our group developed vaccines based on the genetic fusion of the HSV-1 glycoprotein D (gD) with the HPV-16 E7 oncoprotein (gDE7 vaccines). Despite the promising antitumor results reached by gDE7 vaccines in mice, combined therapies may increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Regarding cervical cancer (CC), inhibition of IDO-1 (Navoximod) in combination with atezolizumab (PD-L1 inhibitor) has been studied in a phase 1 clinical trial (NCT02471846); however, antitumoral effectiveness was partial [ 36 ]. Recently, it was observed that IDO-1 inhibitors (D-1MT and DL-1MT) enhance the antitumor effect of the HPV16 E7 oncoprotein vaccine (gDE7) [ 59 ]. However, it is crucial to note that using IDO-1 inhibitors as a monotherapy approach promotes tumor growth [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding cervical cancer (CC), inhibition of IDO-1 (Navoximod) in combination with atezolizumab (PD-L1 inhibitor) has been studied in a phase 1 clinical trial (NCT02471846); however, antitumoral effectiveness was partial [ 36 ]. Recently, it was observed that IDO-1 inhibitors (D-1MT and DL-1MT) enhance the antitumor effect of the HPV16 E7 oncoprotein vaccine (gDE7) [ 59 ]. However, it is crucial to note that using IDO-1 inhibitors as a monotherapy approach promotes tumor growth [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treating IL-6 knockout mice with IDO inhibitors was shown to inhibit IDO expression. Furthermore, combination therapy with a therapeutic vaccine resulted in decreased intratumoral polymorphonuclear MDSCs and Treg cells, supporting IL-6 and IDO as immune-metabolic adjuvants for immunotherapies against CC ( 127 ). Considering this preclinical research data, it appears that targeting the suppressive immune cells and metabolites within the TME can be used in combination therapies to boost tumor-specific immunity, further improving the therapeutic antitumor effect.…”
Section: Therapeutic Strategies For Targeting the Tme Of Cervical Cancermentioning
confidence: 93%
“…Treatment of IL-6 knockout mice with IDO inhibitors has been proven to inhibit the expression of IDO. In addition, combination therapy with therapeutic vaccines leads to a decrease in polymorphonuclear MDSCs and Treg cells in tumors, supporting IL-6 and IDO as immunometabolic adjuvants for immunotherapy against CC ( 127 ). Combination therapy targeting inhibitory immune cells and metabolites within the TME represents a new strategy for antitumor therapy.…”
Section: Therapeutic Strategies For Targeting the Tme Of CCmentioning
confidence: 99%